The Covid-19 Pandemic Affecting Tax Compliance of Small and Medium Enterprises in Vietnam - Le Thu Thuy (International Journal of Supply Chain Management, 2021)
The Covid-19 pandemic had a significant impact on the socio-economic situation in Vietnam. The Government is implementing “dual tasks” to prioritize epidemic prevention while promoting production and business, promoting patriotism, and calling for business colleagues to turn challenges into opportunities, create a driving force for development and re-start the country’s economy. Thus, the study surveyed 450 managers related to the tax of SMEs and answered 16 questions. The data collected from June 2020 to December 2020 at SMEs in Vietnam. The authors applied a simple random sampling technique, tested Cronbach’s Alpha and confirmatory factor analysis (CFA), and model testing with Structural Equation Model (SEM) analysis. The finding has three key factors affecting SMEs’ tax compliance in Vietnam with a significance level of 0.01. Finally, this article recommended policies for enhancing tax compliance at SMEs in Vietnam